Rancang Bangun Aplikasi Geotagging Social Report Bencana Banjir - Wisnu Wijaya; Herman Tolle; Agi Putra Kharisma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Flood is the most frequent disaster in Indonesia. The potential of flood disaster requires a change from disaster management should be changed to risk reduction. This can be done by making a map of disaster that can be used as a reference in the effort of pre-disaster handling or regional development planning. Technological advances can facilitate the creation of disaster maps by utilizing the role of the people who play an active role in reporting the incident of flood disaster that occurred arround them. To facilitate the public in reporting the flood disaster, geotagging technology can be used to develop a mobile applications that are used to report the incidence of floods by storing the location point which is then managed into a data information that can be used to development of a map of flood disaster. This app is developed on mobile devices to make it easier for people to report flood disaster at any time. Based on validation testing, the overall functional requirements can run well and in line with the design are made. In addition, usability testing that includes usefulness, ease of use, ease of learning, and satisfaction produces an average of 86.1%, so it can be concluded that the application of geotagging social report of flood disaster can easily be used by the public.